2006
DOI: 10.1097/00124645-200603000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Your Educational Plan

Abstract: The authors discuss a descriptive educational needs assessment survey based on Benner's Skill Acquisition Model to determine staff nurses' perception of quantity and relevance of educational programs offered to nurses. The evaluations of the feedback received, such as lack of knowledge of available educational offerings and the need to expand the current curriculum, are presented. The main assumption that course offerings have changed or validated practice was supported. Changes based on the information obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…An education that emphasizes learning and enhancing the students’ skills is rooted in the accurate analysis of professional duties and is responsible for improving the students’ knowledge, attitudes, and skills for aiding an excellent performance of professional duties in the future. Clinical nursing teachers ought to possess four important features, i.e., professional competence, interpersonal communication, a personality suitable for nursing, and the ability to teach ( 48 ), and they also should equip their students with the required competence for providing safe, quality clinical care according to clinical evidence ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…An education that emphasizes learning and enhancing the students’ skills is rooted in the accurate analysis of professional duties and is responsible for improving the students’ knowledge, attitudes, and skills for aiding an excellent performance of professional duties in the future. Clinical nursing teachers ought to possess four important features, i.e., professional competence, interpersonal communication, a personality suitable for nursing, and the ability to teach ( 48 ), and they also should equip their students with the required competence for providing safe, quality clinical care according to clinical evidence ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…We understood from the nurses’ interviews that continuous and frequent theoretical education has been beneficial. Others studies have also shown that continuous education could affect nursing practices effectively (18), and that disaster aid education can decrease mortality rates, improve health indices, and decrease disaster expenses (2). In a study by Shadel et al participants were in favor of 30 to 60 minutes sessions and suggested methods of learning such as video records, train-the trainer, and paper-based self-learning packages (19).…”
Section: Discussionmentioning
confidence: 99%